Żywot św. Symeona Słupnika Młodszego z Cudownej Góry w roli paratekstu w jednym z odpisów "Latopisu nowogrodzkiego czwartego" - Brzozowska, Zofia (Vox Patrum, 2026)
Symeon Stylites the Younger (521–592), also known in the Byzantine-Orthodox tradition as St. Symeon of the Admirable Mountain, is probably one of the most famous and best-documented Syrian ascetics. Many hagiographic works devoted to him have been preserved in Syrian, Arabic, Georgian, Greek and Church Slavic literatures. The corpus of Greek texts is quite extensive and includes two long biographies, several abridged lives and their redactions for the needs of Byzantine liturgical books. Both versions of the Greek extensive life (BHG 1689 and 1690) and several versions of the prologue life were translated into Church Slavic. This article presents a variant of the life of St. Symeon Stylites the Younger taken from the verse prologue, written on the last, free page of the mid-16th-century manuscript containing the Novgorod Fourth Letopis (historical work from the 15th century) as a gloss-paratext. This shows the extraordinary durability of the Byzantine hagiographic tradition in the culture of the Eastern Slavs until the 16th century.